Factors Influencing Readiness of Livestock Farmers to Adopt ICTs: The Case of Barnala District, Punjab - Singh, Sureyndra; TANWAR, PRAHALAD SINGH; Sharma, Anjuly (Indian Journal of Extension Education, 2023)
A study was conducted to determine the propensity of livestock farmers to adopt ICTs in the Barnala district of Punjab, India. The convenience sampling technique was used to select 60 livestock farmers from all three blocks of the Barnala district and the data was collected from respondent livestock farmers via direct interview using a pre-formulated schedule. Livestock farmers were using ICT (GADVASU apps) to enhance their farm income. The commonly used ICT tools were mobile phones, Internet browsing, newspapers, and television. The use of ICT (GADVASU apps) by livestock farmers was effective as it contributed to enhancing livestock productivity. Socioeconomic and institutional factors significantly influenced the use and adoption of ICTs by livestock farmers. Tobit analysis results indicated that age, education level, herd size, and participation in extension activities were significant (p≤ 0.1) determining factors influencing the adoption of ICTs. Farmers have small herd sizes, little experience using ICT, and higher education levels. Adoption of ICTs (GADVASU apps) may be sustainable among livestock farmers if the extension agencies prioritize developing strategies and programmes to educate farmers. The government also subsidies farmers so that they can purchase data and ICT tools.